Aggressive confrontation shapes perceptions and attitudes toward racist content online. (September 2020) - Meyers, Chanel; Leon, Angelica; Williams, Amanda
With more people using social media on a daily basis and the prevalence of racial discrimination online, it becomes imperative to understand what factors impact minority individuals' perceptions of these transgressions in an online context. Confrontation to discrimination in the form of comments on social media may meaningfully shape perceptions of racism online. Across three studies, we examine how confrontation type (aggressive vs. passive) and confronter group membership (ingroup vs. outgroup) influence Asian Americans' perceptions of online prejudice and attitudes towards the confronters. In Study 1, we find that aggressive confrontations alter perceptions of a racist online post to be more offensive as compared to passive confrontations. In Study 2, these findings extend to participants' likelihood to report the content as offensive. Lastly, in Study 3, we find that aggressive confronters are evaluated more positively than passive confronters. These findings have important implications for understanding racial discrimination in an online context by demonstrating the impact of confrontation type on minority individuals' perceptions and behaviors.